New Specimen of the Enigmatic Dicynodont Lanthanostegus mohoii (Therapsida, Anomodontia) from the Southwestern Karoo Basin of South Africa, and its Implications for Middle Permian Biostratigraphy - Rubidge, Bruce S.; Day, Michael O.; Benoit, Julien (Frontiers in Earth Science, 2021)
Lanthanostegus is an unusual dicynodont known from only two partial skulls from a single locality near Jansenville in the Eastern Cape Province of South Africa. Although these specimens can be constrained to near the base of the late middle Permian (Guadalupian) Abrahamskraal Formation, their precise age is uncertain as a result of diachroneity of the base of the Formation and the absence, in the Jansenville area, of index taxa to correlate this horizon with the biostratigraphy established in the Western Cape Province. Here, we describe a third skull that we identify as Lanthanostegus, which we recently discovered from a locality north of Laingsburg, on the western side of the main Karoo Basin. This skull reveals morphological details of the palate, occiput, and lower jaw that are not preserved in the described specimens of Lanthanostegus mohoii and will advance understanding of this poorly known dicynodont. This discovery provides the first direct correlation between the lower Abrahamskraal Formation at Jansenville on the eastern side of the basin and the southwestern part of the basin, and suggests that Lanthanostegus occurs in the lowest Tapinocephalus Assemblage Zone (AZ), or possibly to a new assemblage transitional between the Eodicynodon and Tapinocephalus AZs. This supports earlier work proposing that the Eodicynodon AZ is present only on the western side of the Karoo Basin and that the transition from a marine to continental depositional environment occurred later toward the East.